2014
DOI: 10.3923/pjbs.2014.947.951
|View full text |Cite
|
Sign up to set email alerts
|

Fluctuation of Diptera Larvae in Phytotelmata and Relation with Climate Variation in West Sumatra Indonesia

Abstract: Research of fluctuations in Diptera's larvae in Phytotelmata had been conducted at three locations in West Sumatra, Indonesia; Padang, Bukittinggi and Payakumbuh; which aimed to determine the number and fluctuations Diptera larvae in Phytotelmata. The results obtained; the highest number of individual larvae Diptera in Phytotelmata was 7109 Aedes albopictus larvae (49.56%), followed by larvae of Culex tritaeniorhynchus with 2409 individuals (16.80%). Larvae fluctuated every month and tent to increase in Novemb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Previous studies have shown that early detection of potential outbreaks of arbovirus through mosquito surveillance is an effective method for dengue mitigation. [17][18][19][20] In this study, we highlight the possibility of mosquito surveillance for arbovirus as an approach for dengue mitigation in Bandung city, West Java, Indonesia. Results showed that arboviral RNA can be detected in mosquitoes captured from two villages, one of which tested positive for dengue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that early detection of potential outbreaks of arbovirus through mosquito surveillance is an effective method for dengue mitigation. [17][18][19][20] In this study, we highlight the possibility of mosquito surveillance for arbovirus as an approach for dengue mitigation in Bandung city, West Java, Indonesia. Results showed that arboviral RNA can be detected in mosquitoes captured from two villages, one of which tested positive for dengue.…”
Section: Discussionmentioning
confidence: 99%
“…16 This method has been applied for the early detection of potential outbreaks and to identify new arbovirus agents. 17,18 Detecting the circulation of the dengue virus in mosquitoes could prevent future outbursts of dengue disease, especially in regions with the co-circulation of multiple arboviruses. 19,20 Initially, arbovirus detection in mosquitoes was based on the viral antigen, using enzymelinked immunoabsorbent assay (ELISA) or immunofluorescence assay (IFA).…”
Section: Introductionmentioning
confidence: 99%
“…We also characterized the microbial communities associated with each treatment and their relationship with mosquito survival and development. Aedes albopictus occur in a variety of natural (phytotelmata) and artificial (Rosa et al 2014;Unlu et al 2013) containers (e.g. waste tires, plant saucers) that are likely to be exposed to fertilizers emanating from farm activities in urban and suburban areas.…”
Section: Introductionmentioning
confidence: 99%